PENINGKATAN KOMPETENSI GURU PAI PADA PELAKSANAAN PEMBELAJARAN JARAK JAUH (PJJ) DI MASA PANDEMI COVID-19 - Diana Diana; Nazik Rida’i; Syintia Aulia (el-Moona: Jurnal Ilmu Pendidikan Islam, 2022)
Covid-19 causes learning to be a different pattern, to avoid transmitting the virus.Soschools carry out learning using the internet network. Teachers can use applications that match the material. The purpose of the study was to obtain and reveal the efforts of PAI teachers in dealing with teaching and learning activities during the Covid-19 period at MIN 1 Tangerang. This research was conducted at MIN 1 Tangerang using a qualitative approach. Data was collected through interviews, observation, and documentation. The results of this study, firstly, found that PAI teachers actively participated in online webinars every time there was training from the KKG PAI Tangerang Regency and took online webinars held from the Tangerang Regency Education Office and participated in training from Banten Province KKG. Second, revealing that PAI teachers have realized the importance of technology and applications for learning during the Covid-19 pande.